2012
DOI: 10.1158/0008-5472.can-11-3248
|View full text |Cite
|
Sign up to set email alerts
|

DNA Methylation Does Not Stably Lock Gene Expression but Instead Serves as a Molecular Mark for Gene Silencing Memory

Abstract: DNA methylation is commonly thought of as a "molecular lock" that leads to permanent gene silencing. To investigate this notion, we tested 24 different HDAC inhibitors (HDACi) on colon cancer cells that harbor a GFP locus stably integrated and silenced by a hypermethylated CMV promoter. We found that HDACi efficiently reactivated expression of GFP and many other endogenous genes silenced by DNA hypermethylation. After treatment, all promoters were marked with active chromatin, yet DNA hypermethylation did not … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
119
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(127 citation statements)
references
References 24 publications
5
119
2
Order By: Relevance
“…17 DNA methylation at transcription start sites and gene promoters has been associated with the formation of heterochromatin and long-term gene silencing. 30,31 Methylation is also an inactivating mechanism of the tumour suppressor p16 gene in MM, which is associated with high plasma cell proliferation and short survival. 32 Furthermore, p16 methylation may be a marker for overall epigenetic changes associated with disease progression.…”
Section: Dna Methylationmentioning
confidence: 99%
“…17 DNA methylation at transcription start sites and gene promoters has been associated with the formation of heterochromatin and long-term gene silencing. 30,31 Methylation is also an inactivating mechanism of the tumour suppressor p16 gene in MM, which is associated with high plasma cell proliferation and short survival. 32 Furthermore, p16 methylation may be a marker for overall epigenetic changes associated with disease progression.…”
Section: Dna Methylationmentioning
confidence: 99%
“…There are HDIs currently in clinical trials; however, less data is available for their use in MDS, though anecdotal responses have been reported [75]. Recently, it has also been reported that DNA methylation per se is not a permanent lock for silencing gene expression, but rather a combination of DNA methylation inhibitors with other drugs (such as HDIs) can be used to reactivate gene expression [76,77]. Furthermore, there is increasing evidence that such combinations have encouraging results [78,79].…”
Section: Epigenetic Therapymentioning
confidence: 99%
“…The use of a DNA Methyl Transferase (DNMT) inhibitor followed by an HDAC inhibitor is required for the re-expression of genes silenced by promoter hypermethylation. Consequently, the sequential or overlapping combination of DNA hypomethylating agents and HDAC inhibitors has been utilized in several clinical trials based on this hypothesis [2,3].Although few previous reports did not support this hypothesis, they were considered exceptions for specific genes or for a specific class of HDAC inhibitors (SIRT1 inhibitors) [4][5][6]. Recently, a more comprehensive study challenged this hypothesis and demonstrated that different classes of HDAC inhibitors induce transient expression of promoter hypermethylated genes without the loss of DNA promoter hypermethylation [5].…”
mentioning
confidence: 99%
“…Recently, a more comprehensive study challenged this hypothesis and demonstrated that different classes of HDAC inhibitors induce transient expression of promoter hypermethylated genes without the loss of DNA promoter hypermethylation [5]. On the other hand, DNA hypomethylating agents induced permanent and stable epigenetic reprogramming.…”
mentioning
confidence: 99%
See 1 more Smart Citation